Concept of collaboration in the context of Lithuanian history - Tininis, Vytautas (Genocidas ir rezistencija, 2001)
This article analyses collaboration as a phenomenon from legal, political, and moral dimensions. Collaboration is not only a political but also a moral issue. Collaboration with the invading force is shameful and reprehensible. Admittedly, life is very complicated, and it is impossible to predict how to behave in difficult circumstances, but bootlicking and groveling the enemy is always immoral.
Keywords: collaboration; communist party; Soviet occupation; German occupation